Breastfeeding practices in Masaya, Nicaragua: a facility based cross-sectional study - Aleisha M. Nabower; Elizabeth R. Lyden; Francisco J. Rodriguez; Shirley F. Delair (BMC, 2020)
Abstract Background The World Health Organization recommends exclusive breastfeeding for 6 months and total breastfeeding for at least 2 years. Despite this and multiple interventions promoting breastfeeding, early breastfeeding cessation remains high with little data as to the ongoing barriers contributing to early cessation. Methods Two groups of Nicaraguan mothers in an urban hospital were approached to complete a questionnaire to determine what newborn, maternal, and socioeconomic factors contributed to early cessation of breastfeeding. Group 1 participants were mothers of newborns in the newborn units, while group 2 were mothers of children 5 years or younger in the emergency room and pediatric ward. Descriptive statistics summarized the data. Fisher's exact test evaluated factors associated with early breastfeeding cessation. Results In group 1, 97 participants were enrolled with 81% of mothers planning to fulfill the guideline for exclusive breastfeeding for 6 months. In group 2, there were 139 mothers of which 58% reported they had exclusively breastfed for 6 months. Only 25 and 27% of mothers in group 1 and 2 respectively planned to breastfeed or breastfed for 2 years. In group 1, mothers reported lack of knowledge regarding breastfeeding techniques and older mothers tended to plan for early cessation of exclusive breastfeeding. In group 2, mothers reported feeling uncomfortable with breastfeeding in public or had difficulty with latching. Cessation of any breastfeeding prior to 12 months was associated with being uncomfortable breastfeeding in public and knowing the WHO guidelines. In both groups, social media represented an expanding platform for receiving breastfeeding information. Conclusions Interventions focusing on reaching younger mothers and addressing breastfeeding knowledge and techniques while leveraging the increasing influence of social media platforms may help improve compliance with breastfeeding recommendations.